2015
DOI: 10.1002/jms.3568
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of peptide adducts with carbonylated lipid peroxidation products

Abstract: Highly reactive lipid peroxidation-derived carbonyls (oxoLPP) modify protein nucleophiles via Michael addition or Schiff base formation. Once formed, Michael adducts can be further stabilized via cyclic hemiacetals with or without loss of water. Depending on the mechanism of their formation, peptide-oxoLPP can carry aldehyde or keto groups and thus be a part of the total protein carbonylation level. If a carbonyl function is lost during consecutive reactions, the oxoLPP-peptide adducts will not be detected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Peptide/protein modifications by electrophilic lipids esterified to phospholipids have rarely been considered [3] . Recently, several groups have identified adducts of RCS derived from phosphatidylcholine with His, Cys and Lys in synthetic peptides of ApoA and ApoB-100 [75,76] . This is a field of research that should be explored further since adducts of proteins with oxidized phospholipids have been detected in HDL and in human platelets enriched with electrophilic truncated oxidized phosphatidylcholine (KODA-phospahtidylcholine) [77] .…”
Section: Analysis Of Protein Lipoxidation Through Ms-based Methodsmentioning
confidence: 99%
“…Peptide/protein modifications by electrophilic lipids esterified to phospholipids have rarely been considered [3] . Recently, several groups have identified adducts of RCS derived from phosphatidylcholine with His, Cys and Lys in synthetic peptides of ApoA and ApoB-100 [75,76] . This is a field of research that should be explored further since adducts of proteins with oxidized phospholipids have been detected in HDL and in human platelets enriched with electrophilic truncated oxidized phosphatidylcholine (KODA-phospahtidylcholine) [77] .…”
Section: Analysis Of Protein Lipoxidation Through Ms-based Methodsmentioning
confidence: 99%
“…The detection of protein‐oxoLPP in complex biological matrices relies on either specific immunoassays or sensitive mass spectrometry techniques, though the analysis of PL‐oxoLPP–protein adducts is challenged in reversed phase chromatography‐MS by the physicochemical properties, relatively low quantities in biological samples, and multiple positional isomers. Recently, we analyzed peptides modified by oxoLPP and PL‐bound oxoLPP, in mixtures containing also oxidized lipids and unmodified peptides using hydrophilic interaction liquid chromatography (HILIC) coupled on‐line to electrospray ionization (ESI)‐MS . Although this approach identified many peptide modifications resulting from PL oxoLPP, it was not possible to identify (positional) isomers most likely present in the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Small aldehydes generated by lipid oxidation, for example, malondialdehyde (MDA), acrolein (ACR), or 4‐hydroxynonenal (4‐HNE) are harmful substances upon formation of imines or other, more stable structures ,. Although several studies on small aldehydes have been reported, knowledge of lipid core aldehydes, that is, aldehydes still bound to the parent skeleton, has remained elusive .…”
Section: Figurementioning
confidence: 99%